Adverse events following immunization and vaccine perception in nursing students - Santangelo, O. E.; Provenzano, S.; Grigis, D.; Migliore, C. B.; Firenze, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Vaccines are one of the most successful and cost-effective public health interventions of modern times. This cross-sectional study investigated the perception of vaccinations and potential risks of adverse events following immunization among nursing students. Materials and Methods. An anonymous, self-administered questionnaire was distributed to students undertaking a nursing degree course at the University of Palermo. This questionnaire consisted of three sections: the first part focused on socio-demographic information; the second part contained one question regarding the terms associated with vaccination; and the third part posed a question regarding adverse reactions after immunization. A multivariable logistic regression model was used and adjusted Odds Ratios will be presented in this paper. Results. The sample consisted of 403 students and the mean age was 22.0 years (±3.0). Having considered the dependent variable “Have you ever had adverse reactions after being vaccinated? Moderate-severe”, the statistically-significant independent variables were: the second (adjusted Odds Ratios 0.32) and third (adjusted Odds Ratios 0.18) years of study, the nursing students perceiving their economic and health status to be low (adjusted Odds Ratios 3.52 and 15.92 respectively). The following items from questionnaire were found to be associated with the term vaccination: “I associate the term vaccination with fear” (adjusted Odds Ratios 4.98) and “I do not associate the term vaccination with fighting illnesses” (adjusted Odds Ratios 10.02). Conclusions. Although vaccines are generally safe if used correctly, no vaccination is completely risk-free. There was a general awareness of adverse events following immunization among nursing students in this study. The future healthcare workers have been identified as the most important information source regarding potential solutions in a rapidly evolving health scenario in fighting vaccine hesitancy.